Work Accident Risk Analysis in Tukad Ayung Bridge Replacement Project - Yatana, Ida Bagus Made; Wahyuni, Putu Ika; Muka, I Wayan (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Analysis of the risk of work accidents in the Tukad Ayung Bridge replacement project needs to be carried out by identifying, assessing, and controlling risks using the HIRARC method. This study aims to conduct a work accident risk analysis in the Tukad Ayung Bridge replacement project, precisely in the implementation of concrete girder installation. The data used are qualitative and quantitative data with primary data sources and secondary data. The data collection techniques used are observation, interviews, questionnaires, literature studies, and documentation studies. The data analysis technique used is HIRARC. The results showed that; 1) There are 24 types of work accident risks identified in the concrete girder installation work in the Tukad Ayung bridge replacement project in seven stages of work, namely, the concrete girder preparation stage, girder truss making, erection (segmental girder setting), prestressed steel installation (strand), strand cable stressing work, girder concrete tendon grouting, and diaphragm installation stage, 2) The results of risk analysis on concrete girder installation work on the project The replacement of the Tukad Ayung Bridge, is in the moderate category, which is as many as 12 risks with a percentage of 50%. Furthermore, as many as 11 risks are included in the high category with a percentage of 45.837%. Meanwhile, in the extreme category as much as one risk with a percentage of 4.17%, 3) Risk control efforts that can be carried out from the three levels of risk found, namely moderate, high, and extreme, namely by reducing risk through administrative control, engineering control, and warning system.